Formation of an investment portfolio adequate for stochasticity of profit possibilities - Rutkauskas, Aleksandras Vytautas; Stankevičienė, Jelena (Journal of Business Economics and Management, 2003)
The paper deals with the conception of integrated bank assets and liabilities portfolio adequate to stochastic nature of assets profitability and liabilities expenditures. Two interconnected situations are considered. Firstly, the principles of construction of an investment portfolio, adequate to stochastic nature of an investment yield arc considered. Further, the idea of consideration and optimal selection of integrated assets and liabilities portfolio is considered. These problems are solved on the basis of the authors’ idea of investment portfolio adequate for stochastic nature of investment portfolio and the numerical solution of such problems, which is briefly presented.First Published Online: 14 Oct 2010